Implementation of the Kurikulum Merdeka on productive subjects in the Accounting Department - Maula Diah Liani; Delisa Hafidah; Agni Nazwa N; Ahnaf Daris Fadhilah (Curricula: Journal of Curriculum Development, 2025)
The curriculum applied in the world of education has always undergone many changes, both in terms of objectives and curriculum implementation. Kurikulum Merdeka is a curriculum that has a major influence on the application of learning in Vocational High Schools, which are engaged in theoretical and practical learning. This study aims to analyze the results of implementing the Kurikulum Merdeka on productive accounting subjects in line with applying practices in the industrial world. This research method uses a descriptive qualitative method by collecting information through interviews and observation activities with three resource persons related to the field of curriculum implementation. The results showed that implementing the Kurikulum Merdeka for accounting productive subjects at SMKN 11 Bandung created significant changes from eliminating KKM to merging productive subject assessments. Kurikulum Merdeka fosters students in mastering academic competencies and soft skills through Praktik Kerja Lapangan (PKL) and Uji Kompetensi Keahlian (UKK). The integration of the use of Microsoft Excel, MYOB, and Accurate tools and the creation of entrepreneurial projects also play a role in developing student skills in line with the needs of the world of work.   Abstrak Kurikulum yang diterapkan dalam dunia pendidikan senantiasa mengalami banyak perubahan baik dari sisi tujuan hingga implementasi kurikulum. Kurikulum Merdeka menjadi kurikulum yang memberikan pengaruh besar terhadap penerapan pembelajaran pada Sekolah Menengah Kejuruan yang bergerak dalam bidang pembelajaran teori dan praktik. Penelitian ini bertujuan untuk menganalisis hasil implementasi Kurikulum Merdeka terhadap mata pelajaran produktif akuntansi yang sejalan dengan penerapan praktik dalam dunia industri. Metode penelitian ini menggunakan metode kualitatif deskriptif dengan pengumpulan informasi melalui kegiatan wawancara serta observasi kepada 3 narasumber yang berkaitan dengan bidang penerapan kurikulum. Hasil penelitian menunjukkan bahwa pengimplementasian Kurikulum Merdeka terhadap mata pelajaran produktif akuntansi di SMKN 11 Bandung menciptakan perubahan yang signifikan dari mulai penghapusan KKM hingga penggabungan penilaian mata pelajaran produktif. Kurikulum Merdeka membina peserta didik dalam penguasaan kompetensi akademis dan softskill melalui kegiatan Praktik Kerja Lapangan (PKL) dan Uji Kompetensi Keahlian (UKK). Integrasi penggunaan perangkat Microsoft Excel, MYOB, dan Accurate serta penciptaan proyek kewirausahaan pun berperan dalam pengembangan keterampilan peserta didik yang sejalan dengan kebutuhan dunia kerja. Kata Kunci: Akuntansi; Implementasi; Kurikulum Merdeka; Mata Pelajaran Produktif